Pemanfaatan Kombinasi Daun Kelor Dan Ikan Gabus Mengatasi Anemia Dan Penurunan Protein Pada Lansia Di Panti Lansia - Nur Fitria, Cemy; Prabowo, Anis; Mintarsih, Sri; Mahmudah, Aisyah Na’imatul; Saputri, Wulan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Anemia in the elderly often occured chronically. Attention to anemia in the elderly is very lacking compared to women of childbearing age. The condition of the elderly is usually degenerative and food intake decreases, causing the condition of their body protein to decrease. Albumin protein in the elderly is still very much needed to affect the brain, bone and muscle mass, immune system, metabolism, and health of hair, skin, and nails. The purpose of utilizing local wisdom materials in the form of a combination of moringa leaf powder and snakehead fish has social and economic impacts. The elderly who have received this nutrition will improve their health. The activity method is the lecture method, discussion and coercion, and is applied directly by giving drinks to the elderly. Results of community service activities. The elderly experienced an increase in Hemoglobin after being given a combination of moringa leaf powder and snakehead fish by an average of 2 gr% and blood protein of 1.1 g dl before and after being given a combination of moringa leaf powder and snakehead fish.